Advancing liver cancer treatment with dual-targeting CAR-T therapy - Ze Yang; Chao Cheng; Zhongliang Li; Huajing Wang; Mengmei Zhang; Ermin Xie; Xu He; Bing Liu; Hongwei Sun; Jiantao Wang; Xiaopei Li; Dingjie Liu; et al. (Journal of Nanobiotechnology)
Abstract Chimeric antigen receptor (CAR)-T cell therapy targeting glypican-3 (GPC3) has shown promise in the treatment of hepatocellular carcinoma (HCC). However, the efficacy of CAR-T cells that focus solely on cell surface tumor-associated antigens is often limited. To overcome this challenge, we developed a dual-targeting CAR-T cell strategy. The intracellular alpha-fetoprotein (AFP) antigen, a well-established biomarker of liver cancer, presents the immunogenic Human Leukocyte Antigen (HLA)-A*02:01-restricted epitope 158–166. Consequently, we engineered a T cell receptor (TCR) mimic antibody with high specificity and affinity, providing a promising therapeutic avenue to target this critical antigen. To enhance treatment outcomes for liver cancer, we further modified previously developed GPC3 CAR-T cells, which demonstrated robust anti-tumor efficacy against GPC3-high tumor cells, to secrete an optimized bispecific T cell engager (BiTE) targeting the presented AFP antigen. This dual-targeting strategy significantly improved CAR-T cell proliferation and persistence, as well as enhancing cytokine expression and anti-tumor activity against HCC cells, particularly those exhibiting low GPC3 and AFP expression, both in vitro and in vivo. Our findings highlight the potential of this innovative approach to offer more effective treatment options for patients with liver cancer. Graphical sbstract